GP IIb/IIIa-Mediated Platelet Activation and Its Modulation of the Immune Response of Monocytes Against Candida albicans - Zheng, Lin; Duan, Zhimin; Tang, Dingjie; He, Yanzhi; Chen, Xu; Chen, Qing; Li, Min (Frontiers in Cellular and Infection Microbiology, 2021)
Candida albicans is the most common fungal pathogen in humans, causing invasive disease and even potentially life-threatening systemic infections when tissue homeostasis is disrupted. Previous studies have identified an essential role of platelets in infection and immunity, especially when they are activated. However, it is still unclear whether platelets can be activated by C. albicans, and even less is known about the role of platelets in C. albicans infection. Herein, we showed that C. albicans induced platelet activation in vitro. C. albicans elevated the levels of AKT Ser473 phosphorylation, and inhibition of the PI3K-AKT signaling pathway reversed C. albicans-induced platelet activation. Surprisingly, C. albicans-induced platelet activation occurred in an integrin glycoprotein (GP) IIb/IIIa-dependent manner but was independent of the pattern recognition receptors toll-like receptor (TLR) 2 and TLR4. Interestingly, platelets enhanced the phagocytosis of human monocytes challenged with C. albicans and upregulated the expression of inflammatory cytokines, which were dependent on platelet activation mediated by GP IIb/IIIa. The present work provides new insights into the role of activated platelets in the defense against C. albicans, highlighting the importance of GP IIb/IIIa in the recognition of C. albicans.